Revalorization of Vinasse as a Farmland Improver Through Multi-Objective Genetic Algorithms: A Circular Economy Approach - Aarón Montiel-Rosales; Nayeli Montalvo-Romero; Gregorio Fernández-Lambert; Horacio Bautista-Santos; Yair Romero-Romero; Juan Manuel Carrión-Delgado (Land)
Vinasse is a waste generated from the sugarcane ethanol production process. It is an effluent that, when discharged into the environment, causes serious damage. This study evaluated the potential of vinasse as a regenerator of agricultural soil through Multi-Objective Genetic Algorithms (MOGAs). This study focused on optimizing the amount of vinasse that should be applied, depending on its composition and the needs of the agricultural land. The methodology included five phases where the properties of the cultivated land with and without vinasse were evaluated; with the experimental data, MOGAs were constructed to evaluate soil: (a) fertility, (b) quality, and (c) health. The vinasse was characterized; meanwhile, to understand how the soil behaves depending on the incorporation of vinasse, a factorial experiment was designed in soils where sugarcane is grown in Mexico. The models were built and optimized using MATLAB® and evaluated using Pareto Front. This study showed that vinasse improved soil fertility, quality, and health, with an optimal ratio of mixture formed by 40% vinasse and 60% irrigation water. This ratio allows the development of appropriate soil conditions for the growth of the crop—this is achieved after the application of the vinasse during the preparation of the land for cultivation, which is reached at approximately 20 cm depth—(a) fertility with K of 150 to 230 mg/kg, P of 25 to 35 mg/kg, and N of 17 to 19 mg/kg; (b) quality with MC of 90 to 95%, OM of 3.5 to 4%, and pH of 6.5 to 7.5 UpH; and (c) health with equity of 78% to 80%, abundance of 75% to 80%, and diversity of 80% to 95%. A comparative analysis between an experimental field with and without vinasse showed a 24% increase (ton/ha) in sugarcane yield. The value of vinasse is highlighted, not only as a waste to be treated, but as a regenerative input aligned with the Circular Economy.